Effect of Potting Media on Growth and Quality parameters of Juniperus polycarpos C. Koch Seedlings under Nursery Condition - Negi, P. S.; Sharma, Sandeep; Thakur, Neha (Indian Forester, 2021)
A trial was conducted to study the effect of different potting media on the growth performance of Juniperus polycarpos under nursery condition. One year old seedlings of J. polycarpos raised in germination beds were transplanted in polybags filled with different combination of potting media with seven treatments comprising various combinations of soil, sand and farmyard manure and five replication in completely randomized design to study their effect on seedling growth and quality parameters. Significant differences were observed in shoot length, collar diameter, root length, number of roots, root and shoot biomass of J. polycarpos seedlings raised in different potting media. Maximum growth of various seedling parameters viz., shoot length (58.80cm), collar diameter (6.98mm), root length (55.24cm), number of roots (58.53) was recorded in treatment T7 i. e. Soil + Sand + FYM (1:1:1) where as minimum growth of various seedling parameters was recorded in treatment T1 i.e. nursery soil. Maximum fresh shoot biomass (32.35 g seedlings-1) was recorded in treatment T4, whereas fresh root biomass (9.08 g seedlings-1) and total fresh biomass (40.85g seedlings-1) was recorded in treatment T7 . Maximum dry shoot biomass (17.33 g seedlings-1) was recorded in treatment T5 whereas dry root biomass (4.60 g seedlings-1) and total dry biomass (21.86g seedlings-1) was recorded in treatment T7. Maximum value of various seedling quality parameters viz., root shoot ratio (0.27), volume index (2864.75) and Quality index (1.79) was also observed in seedling grown in treatment T7 and whereas least value of sturdiness quotient (8.40) was observed in treatment T1 (nursery soil) which is at par with treatment T7. The study recommended raising of seedlings of J. polycarpos in soil, sand and farm yard manure (1:1:1) for production of quality nursery stock.